(untitled) (Journal of Enam Medical College, 2019)
Background: Lower uterine caesarean section is a common mode of delivery now and surgical site infection is one of the most common and dreaded complication of surgery. It is associated with significant morbidity and delayed recovery and it lengthens hospital stay and costs. Identifying risk factors for surgical site infection in caesarean wound and modifying them can be beneficial for patient management during surgery and optimizing good clinical outcome. Identifying microorganisms with their sensitivity has epidemiological as well as therapeutic implications. Objective: To identify risk factors for surgical site infection in caesarean section wound and find out microorganisms responsible for such infection. Materials and Methods: In this study 100 women with surgical site infection after caesarean section were included. They were selected randomly from four maternity units of Dhaka Medical College Hospital. Each patient of caesarean section was followed strictly up to discharge from hospital and also for 30 days postoperatively for any evidence of infection. Wound swab was sent in each case for microbiological study. Data were collected in structured questionnaire and analysed by computer using spreadsheet. Results: Among 100 women studied, 73% had inadequate or no antenatal check-up, 52% had duration of labour pain >12 hours, 52% had duration of ruptured membrane >12 hours, 94% women underwent emergency caesarean section, 62% had operation time >1 hour, 61% had haemoglobin level <60%, 46% women had intervention by untrained birth attendant, and 43% women had >500 mL blood loss during operation. In bacteriological study, microorganisms were identified in 55% cases, among them Staphylococcus aureus (20%), E. coli (11%), Acinetobacter (7%), Pseudomonas (6%) and Proteus (5%). During sensitivity test Staphylococcus aureus was mostly sensitive to ceftriaxone (50%) and amikacin (33%) and E. coli to amikacin (80%). In four cases (2 proteus and 2 pseudomonas) out of 55 organisms were resistant to all antibiotics. Conclusion: Most of the risk factors for surgical site infection during caesarean section identified in this study can be modified through intervention. However, the microorganisms detected from our patients showed a high degree of resistance for commonly prescribed antimicrobials in our set-up. J Enam Med Col 2019; 9(2): 90-96